USING ACCELERATOR PEDAL FORCE TO INCREASE SEAT BELT USE OF SERVICE VEHICLE DRIVERS - Van Houten, Ron (The Society for the Experimental Analysis of Behavior, 2011)
This study evaluated a device that applied a sustained increase in accelerator pedal back force whenever drivers exceeded a preset speed criterion without buckling their seat belts. This force was removed once the belt was fastened. Participants were 6 commercial drivers who operated carpet-cleaning vans. During baseline, no contingency was in place for unbuckled trips. The pedal resistance was introduced via a multiple baseline design across groups. On the first day of treatment, the device was explained and demonstrated for all drivers of the vehicle. The treatment was associated with an immediate sustained increase in seat belt compliance to 100%. Occasionally, drivers initially did not buckle during a trip and encountered the force. In all instances, they buckled within less than 25 s. These results suggest that the increased force was sufficient to set up an establishing operation to reinforce seat belt buckling negatively. Drivers indicated that they were impressed with the device and would not drive very long unbelted with the pedal force in place.